Efficacy of green tea leaf extract (camellia sinensis) with NaOCl 2.5% againts enterococcus faecalis as an alternative solution for root canal irrigation - Aries C. Trilaksana; Adeliana Saraswati (Journal of Dentomaxillofacial Science, 2016)
Enterococcus faecalisÂ is a coccal Gram-positive bacteria with facultative anaerob feature. NaOCl have been proven effective againtsÂ Enterococcus faecalisÂ for root canal irrigation process. Green tea leaf extract (Camellia sinensis) can be chosen as an alternative solution for root canal irrigation. The purpose of this study is to determine the difference of green tea leaf extract (Camellia sinensis) and NaOCl 2.5% efficacy againts the growth ofÂ Enterococcus faecalisÂ bacteria. This is a laboratory experimental study with â€œpost test only groupâ€ design. The first step of the trial was done by making green tea leaf extract and then determine the lowest concentration on which the first solution become clear. The concentration that were tested are 1.5%, 2.5%, 3.5%, 4.5% and 5.5%. Based on the trial, it was found that the minimal inhibiton concentration of the green tea leaf extract was 1.5%. The anti-bacterial effect testing method was using diffusion method to differenciate inhibition zone of the green tea leaf extract solution on various concentrations that were being tested and compare it with NaOCl 2.5%. Each group was replicated three times. The obtained data was analyzed with One Way Anova test and the continued with LSD test. The result of the study is that NaOCl 2.5% have superior anti-bacterial effect againtsÂ Enterococcus faecalisÂ compared to green tea leaf extract.